The formation of a modern Rabbi : the life and times of the Viennese scholar and preacher Adolf Jellinek - Kessler, Samuel Joseph (Brown Judaic studies, 2022)
Adolf Jellinek (1821-1893), the Czech-born, German-educated, liberal chief rabbi of Vienna, was the most famous Jewish preacher in Central Europe in the second half of the nineteenth century. As an innovative rhetorician, Jellinek helped mold and define the modern synagogue sermon into an instrument for expressing Jewish religious and ethical values for a new era. As a historian, Jellinek made groundbreaking contributions to the study of the Zohar and medieval Jewish mysticism. The Formation of a Modern Rabbi discusses the ways in which Jellinek was emblematic of a new synagogue-based model of rabbi-as-scholar-preacher and returns Jellinek to the center of the Jewish nineteenth century-a world in which the role of rabbi, synagogue, and Jewish studies was being reinvented and renewed. --